2019
DOI: 10.1002/hbm.24724
|View full text |Cite
|
Sign up to set email alerts
|

EEG‐based outcome prediction after cardiac arrest with convolutional neural networks: Performance and visualization of discriminative features

Abstract: Prognostication for comatose patients after cardiac arrest is a difficult but essential task. Currently, visual interpretation of electroencephalogram (EEG) is one of the main modality used in outcome prediction. There is a growing interest in computer‐assisted EEG interpretation, either to overcome the possible subjectivity of visual interpretation, or to identify complex features of the EEG signal. We used a one‐dimensional convolutional neural network (CNN) to predict functional outcome based on 19‐channel‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 45 publications
0
36
0
Order By: Relevance
“…This is especially true for electroencephalography (EEG). In patients with HIE, EEG has become the main prognostic tool, as several visual and quantitative (computer-derived) features have been shown to predict functional outcome [6][7][8][9][10][11][12][13]. In particular, a continuous and reactive EEG background suggests a favorable outcome, whereas a suppressed background or burst suppression with identical bursts is usually predictor of poor outcome [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…This is especially true for electroencephalography (EEG). In patients with HIE, EEG has become the main prognostic tool, as several visual and quantitative (computer-derived) features have been shown to predict functional outcome [6][7][8][9][10][11][12][13]. In particular, a continuous and reactive EEG background suggests a favorable outcome, whereas a suppressed background or burst suppression with identical bursts is usually predictor of poor outcome [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…100 Computer-assisted interpretation of early EEG (9-30 hours after CA) during TTM using a convolutional neural network achieved an AUC of 0.885 in discriminating good and poor neurological outcome. 101 Nonetheless, confounding variables such as the effect of hypothermia on EEG or sedatives used during TTM must be considered, 102 although recent studies suggested that sedation required for TTM did not alter the predictive value of standardized EEG interpretation, 93 and EEG patterns were not significantly changed in propofol-sedated patients undergoing TTM (both 33 C and 36 C targets). 103 Computerassisted interpretation of EEG is a promising option and warrants further investigation.…”
Section: Electroencephalogram (Eeg)mentioning
confidence: 99%
“…The CAM-based models have been successfully applied to the classification of muscular dystrophies [35], tumor diagnosis [36], EEG signal interpretation [37] and other medical research fields [38]. The biggest advantage of these models is that it can accurately locate the abnormal positions of features (such as electrical signals, cerebral cortex, pathological images, etc.)…”
Section: Related Workmentioning
confidence: 99%